Mercy and justice: a challenge for contemporary theology - Hahn, Judith; Werner, Gunda (Brill's studies in catholic theology, 2020)
The reconciling community : the rite of penance, past and present / James Dallen -- "...equally a judge and a physician" - questioning Canon 978 1 CIC/1983 from a canonical and pastoral point of view / Rosel Oehmen-Vieregge -- Merciful and just? A tension in contemporary semantics in the doctrinal regulations on the sacrament of penance / Gunda Werner -- Fulfilling mercy? Reconsidering the Jubilee Year regulations on penance and reconciliation / Judith Hahn -- Punishment and reconciliation in this world and the next : the relationship between the penitential discipline of the church and reconciliation with God in the twelfth century / Atria A. Larson -- Justice and mercy : can they be reconciled from a systematic point of view? / Dirk Ansorge -- Misericordia, benevolentia, aequitas? Is there room for mercy in Canon Law? / Michael A. Nobel -- "...as we forgive those who trespass against us..."? Aspects of a theology of forgiveness from a Protestant perspective / Heike Springhart -- Free from burdens? Cultural and social aspects of the concept of reconciliation in Latin America / Sandra Lassak -- What remains? Some answers, and yet more questions / Judith Hahn and Gunda Werner.